Elementary School Teacher Training Model with an Instructional Design Approach Through Adaptation of the Kemp Model: A Development Study at UPTD SDN 3 Batu Tungku - Siti Hajar Nurhasanah; Ahmad Suriansyah; Aslamiah Aslamiah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Teacher training at the elementary school level plays a strategic role in supporting the improvement of learning quality. However, many teacher training programs are still not designed using a systematic instructional design approach and often do not sufficiently reflect teachers' actual needs. This study aims to develop an elementary school teacher training model using an instructional design approach through a simplified adaptation of the Kemp Model, making it more operational and applicable in school contexts. The study employed a Research and Development (R&D) approach and was conducted at UPTD SDN 3 Batu Tungku, involving the school principal and elementary school teachers as participants. The development procedures included training needs analysis, model design, expert validation, limited field testing, and model evaluation and refinement. Data were collected through observations, interviews, questionnaires, document analysis, as well as pre-test and post-test instruments. The expert validation results indicated that the developed training model, training modules, and evaluation instruments were feasible and relevant for implementation in elementary school settings. The results of the limited trial showed that the training model based on the adapted Kemp Model assisted teachers in developing more systematic lesson planning, applying more varied instructional strategies, using learning media more effectively, and conducting assessment and reflection activities in a more structured manner.